Conductive polylactic acid filaments for 3D printed sensors: Experimental electrical and thermal characterization - Riaan Stopforth (Elsevier, 2021)
Conductive additive manufacturing polylactic acid (PLA) filament is a material considered for sensors in the additive manufacturing of products, where conductive material, or sensors are infused into dual material printed parts. An example of these additive manufacturing parts could be a space-confined wearable medical device, which requires 3-dimensional circuitry, or an additive manufacturing circuit board, to be infused within the structure of the device. Some research has been conducted with conductive filament in the additive manufacturing of capacitive and radio frequency applications, yet the usage of it is dependant on the electrical properties. This paper experimentally investigates the electrical properties of the conductive PLA, specifically resistance, resistivity, and linear expansion coefficient, as the temperature of the printed conductive material changes. The samples have been printed with the use of an Anet A8 additive manufacturing printer, using the fused filament fabrication process, with printer settings elaborated in this paper.